Synthesis, Growth and Spectroscopic Studies of L-Alanine Hydrogen Chloride(Lahc) Crystals - S. Perumal, A. S. J. Lucia Rose, P. Selvarajan (Recent Research in Science and Technology, 2010)
L-alanine Hydrogen Chloride (LAHC) salt was synthesized by taking L-alanine and hydrochloric acid in 1:1 molar ratio and the solubility of the synthesized salt in deionized water was determined at different temperatures. Single crystals ofÃ‚Â L-alanineÃ‚Â Hydrogen Chloride (LAHC) were grown by solution method with slow evaporation technique. The grown crystals were characterized by single crystal X-ray diffraction (XRD) analysis, FTIR studies and UV-visible transmittance studies and the NLO activity of the grown crystal has been checked by Second Harmonic Generation (SHG) test.Ã‚Â